Proteomic analysis of human tooth pulp proteomes - Comparison of caries-resistant and caries-susceptible persons - Jágr, Michal; Eckhardt, Adam; Pataridis, Statis; Foltán, René; Myšák, Jaroslav; Mikšík, Ivan (Journal of proteomics, 2016)
UNLABELLED: Most people in the world suffer from dental caries, >90% of adults experience caries on enamel and root surfaces during their life. However, the overall roles of all factors in the development of dental caries still remain unclear and are worthy of recent investigation. In this study we used a proteomic 2D-DIGE approach in connection with MS/MS to investigate the different protein abundances in the tooth pulp of human third molars obtained from caries-resistant and caries-susceptible people. Statistical analysis of the two protein maps obtained on large gel (17cm length) and mini gel (7cm length) followed by nLC-MS/MS analysis enabled the identification of 16 significantly changed spots with unique protein identifications corresponding to 12 non-redundant proteins. Seven proteins exhibited higher and four proteins exhibited lower expression in the caries-resistant samples compared to the caries-susceptible samples. Additionally, one protein (alpha-1-antitrypsin) exhibited both expressions (up and down). Most of the differentially expressed proteins were associated with protein metabolism, energy production, cytoskeletal organization and transport. These differentially expressed proteins are likely involved in the natural resistance or susceptibility of humans to the development of dental caries and suggest that the resistance mechanism is multifactorial. BIOLOGICAL SIGNIFICANCE: Dental caries are not a serious and life-threatening disease, but their healing requires many remedies and takes up a lot of time. Moreover, neglecting the problem may lead to tooth loss, which can strongly reduce the quality of life. Therefore the identifying effective and safe oral medicine and determining the causes of caries-resistance were viewed as the main aims of this study. Our work aims to elucidate the mechanism of natural human resistance to the development of dental caries by studying the proteomes of tooth pulp isolated from patients who displayed different prevalences of tooth caries. This study is the first protein tooth pulp comparison of sound teeth obtained from caries-resistant versus caries-susceptible people.
Keywords: náchylnost k nemoci; odolnost vůči nemocem; zubní dřeň; Dental Pulp; Dental Caries; proteomika; Humans; Proteome; Two-Dimensional Difference Gel Electrophoresis; Caries; DIGE; zubní kaz; lidé; Human tooth pulp; Disease Resistance; Proteomics; Tandem Mass Spectrometry; proteom; Molar, Third; tandemová hmotnostní spektrometrie; molár třetí; dvourozměrná diferenční gelová elektroforéza; Resistance; Disease Susceptibility